(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate sleep quality and identify factors associated with sleep quality among patients with knee osteoarthritis at the Department of Traditional Medicine and Rehabilitation, Cua Dong General Hospital in 2025. Subjects and Methods: A cross-sectional study was conducted on 150 patients with knee osteoarthritis who were treated at the Department of Traditional Medicine and Rehabilitation, Cua Dong General Hospital from March to September 2025. Results: The proportion of patients with poor sleep quality (PSQI > 5) was 64%. Univariate analysis showed that occupation, disease duration, history of psychological trauma, physical exercise, participation in social activities, number of medical comorbidities, Visual Analog Scale (VAS) score, Lequesne index, and radiographic severity of osteoarthritis were associated with sleep quality (p < 0.05). In multivariate analysis, the number of comorbidities remained an independent associated factor (OR = 41.51; 95% CI: 11.62–148.31; p < 0.001). Conclusion: Poor sleep quality was highly prevalent among patients with knee osteoarthritis. Occupation, disease duration, history of psychological trauma, physical exercise, participation in social activities, number of medical comorbidities, VAS score, Lequesne index, and radiographic severity of osteoarthritis were associated with sleep quality. Among these factors, the number of comorbidities was identified as an independent associated factor.